Immuno-enhancing effects of surimi products including functional ingredients in vitro and in vivo zebrafish model - Dong-Hyeon Kim; Heeseob Lee; Hye-Won Yang; You-Jin Jeon (Fisheries and Aquatic Sciences)
Surimi is used to the processed seafoods as well-known common products such as eomook, kamaboko, sausages, and imitation crab meat. Recently, surimi products have been studying to improve their healthy functionalities with addition of bioactive ingredients. In the study, surimi products were prepared with Aloe vera gel powder and Red ginseng extract to enhance immunity, and the evaluated in in vitro and in vivo after digestion of the surimi products. Functional surimi products (FSPs) containing with the ratios of A. vera gel powder to Red ginseng extract from 0.4:0.0 to 0.0:0.4 (referred as A1 to A5) were prepared and compared with a general surimi products for the gel strength and immune-enhancing effects. FSPs showed the protective effects against hydrogen peroxide (H2O2)-induced oxidative stressed Vero cells and promoted nitric oxide (NO) production in RAW264.7 cells and zebrafish larvae. Our results suggested that FSPs with combination of A. vera gel powder and Red ginseng extract can induce the synergistic effect in immunity enhancement. In conclusion, FSPs could be applied to health functional seafood industries, in particular eomook markets with immune-enhancement.